Association between IgE‐mediated allergies and diabetes mellitus type 1 in children and adolescents. Issue 7 (17th July 2015) - Klamt, Sabine; Vogel, Mandy; Kapellen, Thomas M; Hiemisch, Andreas; Prenzel, Freerk; Zachariae, Silke; Ceglarek, Uta; Thiery, Joachim; Kiess, Wieland
<x xml:space="preserve">Abstract</x> Background Type 1 diabetes mellitus (T1DM) is characterized by an immunological reaction that is dominated by type‐1 T helper (Th1) cells, whereas immunoglobulin E (IgE)‐mediated allergies are associated with Th2 cell. According to the Th1/Th2‐hypothesis, the immune system is said to either develop into the direction of Th1 or Th2 cells. This would mean that a child developing T1DM is unlikely to develop an IgE‐mediated allergy and vice versa. Objective The aim of the study was to investigate the association between the prevalence of T1DM and IgE‐mediated allergies. Methods We designed a prospective case control study with 94 children and adolescents with T1DM and 188 age‐ and sex‐matched control children. The basis of our investigations was a questionnaire concerning the family and children's history as to the presence of IgE‐mediated allergies. Moreover, the following blood investigations were done: total serum IgE, specific IgE antibodies to major inhalant allergens, and a multiplex cytokine analysis measuring levels of specific cytokines representing either Th1‐ or Th2‐ cytokines. Results Children with T1DM reported the presence of IgE‐mediated allergies significantly more often than children of the control group. Children with T1DM had significantly higher tumor necrosis factor alpha (TNFα) levels than healthy controls. Levels of interleukin‐2 (IL‐2) and IL‐6 were higher in the groups of children with the presence of a personal history of allergies, regardless of the presence of T1DM. Conclusions Our results suggest that T1DM is associated with a higher risk of a self‐reported presence of IgE‐mediated allergies and that the Th1/Th2‐hypothesis may be an oversimplification.